Higher Order Thinking Skills (HOTS) - Oriented Learning in Geography Learning - Yani, Ahmad; Mulyadi, Asep (Universitas Pendidikan Indonesia, 2022)
Higher Order Thinking Skills (HOTS) can be developed by all cognitive learning models such as discovery learning, and its implementation is relatively easy. The purpose of the research formulated is to want to know the implementation of geography learning that is oriented towards Higher Order Thinking Skills (HOTS) in geography subjects at the high school level and want to know the perceptions of students about geography learning at the high school level. This study used the survey method and obtained 140 geography teachers from all over Indonesia. The results of the research show that geography teachers have adequate competence in HOTS-oriented learning. However, some of them do not understand the principles of HOTS-oriented learning well. In the classroom, they use an expository approach (lectures) rather than inquiry. Steps that need to be taken to improve teachers' understanding of HOTS-oriented learning are through collaboration between teachers to improve their teaching practices or through guided re-variation of teaching practices (microteaching). The focus of the exercise is on the cognitive